2017
DOI: 10.1016/j.jtos.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Review: The function of regulatory T cells at the ocular surface

Abstract: Regulatory T cells (Tregs) are critical modulators of immune homeostasis. Tregs maintain peripheral tolerance to self-antigens, thereby preventing autoimmune disease. Furthermore, Tregs suppress excessive immune responses deleterious to the host. Recent research has deepened our understanding of how Tregs function at the ocular surface. This manuscript describes the classification, the immunosuppressive mechanisms, and the phenotypic plasticity of Tregs. We review the contribution of Tregs to ocular surface au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 130 publications
0
19
0
5
Order By: Relevance
“…In fact, Chauhan et al reported that while Treg frequencies remained unchanged, there was a marked decrease in their potential to suppress the effector Th17 cells in a mouse model of DED. This suggests that dysfunction of Tregs can be presumed to be one of the major causes in ocular anterior segment inflammation such as DED [ 90 , 92 ]. It has also been reported that in vitro- expanded Foxp3 + Tregs maintain a normal phenotype and are capable of suppressing immune-mediated ocular surface inflammation in animal models, with in vitro -expanded Tregs able to more efficiently reduce tear cytokine levels and conjunctival cellular infiltration compared to freshly isolated Tregs [ 93 ].…”
Section: Ocular Surface Disease and Tregsmentioning
confidence: 99%
“…In fact, Chauhan et al reported that while Treg frequencies remained unchanged, there was a marked decrease in their potential to suppress the effector Th17 cells in a mouse model of DED. This suggests that dysfunction of Tregs can be presumed to be one of the major causes in ocular anterior segment inflammation such as DED [ 90 , 92 ]. It has also been reported that in vitro- expanded Foxp3 + Tregs maintain a normal phenotype and are capable of suppressing immune-mediated ocular surface inflammation in animal models, with in vitro -expanded Tregs able to more efficiently reduce tear cytokine levels and conjunctival cellular infiltration compared to freshly isolated Tregs [ 93 ].…”
Section: Ocular Surface Disease and Tregsmentioning
confidence: 99%
“…Так, Foulsham W. и соавт. провели исследования патологической конверсии Tregs в условиях экспериментальной кератопластики высокого риска с использованием трансгенных мышей FoxP3 -lineage [30]. Результаты показали, что воспалительный процесс в глазу (обычно имеющий место при трансплантации высокого риска) приводил к потере экспрессии FoxP3 этой регуляторной субпопуляцией лимфоцитов с изменением их в exTregs, фенотипически идентичные эффекторным Th1-клеткам, играющим одну из ключевых ролей в отторжении трансплантата.…”
Section: иммунный ответ при кератопластикеunclassified
“…9,10 Substantial progress has been made in determining the mechanisms by which host factors, such as recipient bed vascularity and inflammation, influence the immune response to corneal allografts. 16 Studies performed by our laboratory [17][18][19][20][21][22][23][24] and others [25][26][27] indicate the critical contribution of Foxp3 + Tregs to immune tolerance in the setting of corneal transplantation. 16 Studies performed by our laboratory [17][18][19][20][21][22][23][24] and others [25][26][27] indicate the critical contribution of Foxp3 + Tregs to immune tolerance in the setting of corneal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…17,23 The mechanisms by which Tregs exert their immunosuppressive effects remain an area of intense investigation. 18,38 Of note, there is evidence that IL-10 itself provides cytoprotection for hepatocytes, neurons, and brain microvascular endothelial cells. 18,38 Of note, there is evidence that IL-10 itself provides cytoprotection for hepatocytes, neurons, and brain microvascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation